Aesculus parviflora: Bottlebrush Buckeye - Edward Gilman; Ryan W. Klein; Gail Hansen (EDIS)
This document is about the bottlebrush buckeye (Aesculus parviflora), a native shrub from Alabama, South Carolina, and Florida. It describes the plant’s physical characteristics, including its rounded form, dark green foliage, and showy white flowers. The document also covers the plant’s growth conditions, such as its preference for moist, shaded habitats and its hardiness in zones 5 through 9A. Additionally, it highlights the uses and benefits of the bottlebrush buckeye in landscaping, noting its ornamental features, moderate growth rate, and pest resistance. The shrub is recommended for use as a specimen, screen, foundation, or border plant. Original publication date October 1999.